Leishmania major Methionine Sulfoxide Reductase A Is Required for Resistance to Oxidative Stress and Efficient Replication in Macrophages - Sansom, Fiona M. (Public Library of Science, 2013)
Leishmania are protozoan parasites that proliferate within the phagolysome of mammalian macrophages. While a number of anti-oxidant systems in these parasites have been shown to protect against endogenous as well as host-generated reactive oxygen species, the potential role of enzymes involved in the repair of oxidatively damaged proteins remains uncharacterized. The Leishmania spp genomes encode a single putative methionine sulfoxide reductase (MsrA) that could have a role in reducing oxidized free and proteinogenic methionine residues. A GFP-fusion of L. major MsrA was shown to have a cytoplasmic localization by immunofluorescence microscopy and subcellular fractionation. An L. major msrA null mutant, generated by targeted replacement of both chromosomal allelles, was viable in rich medium but was unable to reduce exogenous methionine sulfoxide when cultivated in the presence of this amino acid, indicating that msrA encodes a functional MsrA. The ΔmsrA mutant exhibited increased sensitivity to H(2)O(2) compared to wild type parasites and was unable to proliferate normally in macrophages. Wild type sensitivity to H(2)O(2) and infectivity in macrophages was restored by complementation of the mutant with a plasmid encoding MsrA. Unexpectedly, the ΔmsrA mutant was able to induce normal lesions in susceptible BALB/c indicating that this protein is not essential for pathogenesis in vivo. Our results suggest that Leishmania MsrA contributes to the anti-oxidative defences of these parasites, but that complementary oxidative defence mechansims are up-regulated in lesion amastigotes.